EFFECT OF COST MANAGEMENT STRATEGIES ON OPERATIONAL EFFICIENCY OF BANK OF KIGALI, RWANDA (International Journal of Scientific Research and Management (IJSRM), 2022)
High operational cost is a perennial problem in banking sector in Rwanda. The purpose of this study was to examine the effect of cost management strategies on operational efficiency of commercial banks in Rwanda with special reference to Bank of Kigali. The cost management strategies that formed the specific objectives included recruitment and training, technology and business process re-engineering. The target population was 140 managers of Bank of Kigali. A sample size of 103 calculated from Yamane’s formula was utilized. The study adopted descriptive research design. The study data constituted both primary and secondary data. Primary data was collected using questionnaires which were distributed to the managers. Secondary data was collected from published financial reports of BK. The study adopted purposive, stratified and random sampling techniques. The data was cleaned and entered into SPSS version 22 for processing. Presentation of data was aided by tables and graphics Descriptive analysis involved computing frequencies and percentages. Inferential analysis involved computing Pearson correlation coefficient and regression coefficients. Descriptive findings indicated that majority of respondents were in agreement that recruitment and training, technology and business process re-engineering indeed affect operational efficiency. Correlation analysis findings indicated that Pearson’s correlation coefficient for recruitment and training, technology and business process re-engineering were 0.69, 0.75 and 0.56 which are all positive and significant an indication of a positive association between cost management strategies and operational efficiency. Regression analysis also reported R Squared value of 0.692 an indication that cost management strategies account for 69.2% of operational efficiency variations. Moreover, beta coefficients for recruitment and training, technology and business process re-engineering were found to be positive and significant indicating that there is a positive significant effect of cost management strategies on operational efficiency. This study is of importance to the commercial banks’ management team, BNR and academicians or rather future researchers who wish to explore more in the financial sector.